From odium to bellum: classical scholars at war in Europe and America, 1800–1924. (23rd November 2018) - Stray, Christopher
Abstract: The scholarly wars between British and German academics in World War I are to be seen in the context of a more general odium philologicum which can be traced back to the growth of nationalism in the nineteenth century. The century proved an unsettled period in international relations, with tensions between various European powers affecting competing scholarly programmes, including the establishment of archaeological schools and institutes in Athens and Rome. Thus, before 1914 there is a history of inter-state dynamics which saw a continuing realignment of forces among the scholars of different nations. The chapter goes on to consider the contrasting wartime experiences of scholars and students at Cambridge and Oxford, including Francis Cornford, James Duff Duff, Cyril Bailey, E. R. Dodds, Gilbert Murray, and Alfred Zimmern. Murray explored the parallels between the War and the Peloponnesian War, while other notable classicists, including Arthur Hunt, John Beazley, Frank Adcock, and Dillwyn Knox, deployed their considerable intellectual skills for the War Office Cryptanalytic Bureau or Room 40 at the Admiralty. The views of three American scholars, Paul Shorey, Herbert Weir Smyth, and Basil Gildersleeve, serve to further highlight a wide range of opinions and responses to Germany and the War.